Eulerian Oil Spills Model Using Finite-Volume Method with Moving Boundary and Wet-Dry Fronts - Ehsan Sarhadi Zadeh; Kourosh Hejazi (Modelling and Simulation in Engineering)
The world production of crude oil is about 3 billion tons per year. The overall objective of the model in present study is supporting the decision makers in planning and conducting preventive and emergency interventions. The conservative equation for the slick dynamics was derived from layer-averaged Navier-Stokes (LNS) equations, averaged over the slick thickness. Eulerian approach is applied across the model, based on nonlinear shallow water Reynolds-averaged Navier-Stokes (RANS) equations. Depth-integrated standard k-ε turbulence schemes have been included in the model. Wetting and drying fronts of intertidal zone and moving boundary are treated within the numerical model. A highly accurate algorithm based on a fourth-degree accurate shape function has been used through an alternating-direction implicit (ADI) scheme which separates the operators into locally one-dimensional (LOD) components. The solution has been achieved by the application of KPENTA algorithm for the set of the flow equations which constitutes a pentadiagonal matrix. Hydrodynamic model was validated for a channel with a sudden expansion in width. For validation of oil spill model, predicted results are compared with experimental data from a physical modeling of oil spill in a laboratory wave basin under controlled conditions.